How perceived autonomy support and controlling coach behaviors are related to well- and ill-being in elite soccer players: A within-person changes and between-person differences analysis. (January 2017) - Cheval, Boris; Chalabaev, Aïna; Quested, Eleanor; Courvoisier, Delphine S.; Sarrazin, Philippe
Abstract: Objectives: Grounded in Basic Psychological Needs Theory (Ryan & Deci, 2002), this study examined the temporal relationships between perception of coaches' autonomy support and different facets of controlling behaviors, the satisfaction-frustration of athletes' basic needs, and subjective vitality, self-esteem and burnout in elite sportsmen. Methods: Participants (N = 110 males) from three elite youth soccer academies in northwest France completed a questionnaire on three occasions during the last three months of the competitive season. Results: Linear mixed models revealed that perceptions of coach-autonomy support and only two facets of controlling coach behaviors (excessive personal control and negative conditional regard) were related to basic need satisfaction-frustration, which in turn were related to the indices of well- and ill-being. In most cases, the relationships were observed both at the within- and between-person levels, but some were observed only at one level. Conclusions: The findings highlight the importance of considering the different facets of controlling coach behaviors separately and disaggregating the between-person and within-person effects. Highlights: Only negative conditional regard and excessive personal control are related to needs. Autonomy support is only related to relatedness toward coach and teammates. Results are different at the within and between-person levels. Well- and ill-being are mostly associated with autonomy and competence. Coach relatedness and peer relatedness are not related in the same way to well- and ill-being.